Surface oceanographic data (TSG) during Maria S. Merian cruise MSM54 - Johannes Karstensen; Gerd Krahmann (PANGAEA, 2022)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems. Usually, the systems are changed after 12 hours. While temperature is taken at the water inlet in about 6.5 m depth, salinity is estimated within the interior measurement container from conductivity and interior temperature. The data has been compared with CTD data from 5 dbar . This data has not been checked for outliers or noisy data caused by blocked thermosalinograph pumps. Please use with caution.